Costacopluma (Decapoda: Brachyura: Retroplumidae) from the Maastrichtian and Paleocene of Senegal: A survivor of K/Pg events. (January 2016) - Hyžný, Matúš; Perrier, Vincent; Robin, Ninon; Martin, Jeremy E.; Sarr, Raphaël
Abstract: Newly collected decapod material from the Cap de Naze Formation (middle–upper Maastrichtian), Senegal, allows description of a new species of Costacopluma (Brachyura: Retroplumidae), which is older than Costacopluma senegalensis (Remy in Gorodiski & Remy, 1959) from the Paleocene of Senegal and documents that the genus survived the end Cretaceous event in the same area. The holotype of Costacopluma mamethioupamei n. sp. is preserved both in dorsal and ventral aspects, and it bears a strange dumbbell-shaped "scar" on sternite 4 which is tentatively interpreted as a true epibiont mark or remain, which encrusted the crab cuticle syn - vivo or post - mortem ; the identification of the tracemaker is obscured. The cuticular microstructure of Costacopluma mamethioupamei n. sp. is documented using SEM imaging. The cuticle appears to be preserved in its entirety and areas with damaged cuticle shows several distinct layers interpreted as endocuticle, exocuticle and epicuticle. Thanks to the present report of Costacopluma mamethioupamei n. sp. it is now clear that the genus survived the K/Pg boundary not only in the area of the Gulf of Mexico (as documented by several previously published reports) but also in the present-day Senegal. From the palaeobiogeographic perspective, it is interesting to note, that the African continent has been inhabited only with narrow-ridged species of Costacopluma, including Costacopluma concava Collins & Morris, 1975, C . senegalensis and C . mamethioupamei n. sp. This lineage may finally lead to the origin of Tethyan retroplumids, which were widely distributed across Europe during the Eocene. Graphical abstract: Highlights: A new species of retroplumid crab from the Maastrichtian of Senegal is described. Epibiont mark of unknown tracemaker on sternite 4 is documented using SEM. Genus Costacopluma is considered a crab survivor of the K/Pg events. African continent is hypothesized to be a source of Tethyan retroplumids.